2006
DOI: 10.1210/en.2005-1494
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Palmitate But Not Oleate Exposure Induces Endoplasmic Reticulum Stress, Which May Contribute to INS-1 Pancreatic β-Cell Apoptosis

Abstract: Chronic free fatty acid (FFA) exposure induces pancreatic beta-cell death, which may contribute to the development of type 2 diabetes. The mechanisms involved in FFA-induced cell death are not completely understood. Here we have investigated the effect of FFA on endoplasmic reticulum (ER) stress pathways in INS-1 pancreatic beta-cells. INS-1 cells exposed to palmitate for 16-24 h under serum-free conditions showed marked apoptosis and increased protein levels of phosphorylated eukaryotic translation initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
503
11
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(566 citation statements)
references
References 61 publications
(85 reference statements)
41
503
11
6
Order By: Relevance
“…Lethal doses of palmitate enhanced phospho-eIF2a and subsequently induced ATF4 and CHOP in beta cells [11]. Another report demonstrated that palmitate could activate IRE and ATF6 as well as upregulate the ER chaperone machinery including BiP [30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lethal doses of palmitate enhanced phospho-eIF2a and subsequently induced ATF4 and CHOP in beta cells [11]. Another report demonstrated that palmitate could activate IRE and ATF6 as well as upregulate the ER chaperone machinery including BiP [30].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, down-regulation of the IRS/PI3 kinase/Akt signaling pathway was reported to be critical for induction of FFA-induced lipotoxicity [10]. Recently, endoplasmic reticulum (ER) stress was also suggested to be a mediator of FFA-induced beta cell death [11,12].…”
mentioning
confidence: 99%
“…When these mechanisms do not remedy the stress situation, apoptosis is initiated. Since a number of articles have recently reported that ER stress may be implicated in beta cell dysfunction and death in diabetes [10][11][12][13][14][15][16][19][20][21][22][23][24][25][26], in the present study we evaluated features of ER function/dysfunction in human beta cells from type 2 diabetic organ donors. First, we confirmed that diabetic beta cells have functional and survival defects, as previously shown by us and others [27,28,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms causing the loss of beta cell function and mass in type 2 diabetes are still debated [8][9][10]. It has been recently proposed that alterations of endoplasmic reticulum (ER) function in the beta cell contribute to cell dysfunction and death [10][11][12][13][14][15][16]. The ER is central to several important cellular functions, including post-translational modifications, folding and assembly of newly synthesised secretory proteins, and calcium storage [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation